Case report: Complete restoration of the HPA axis function in Cushing’s disease with drug treatment - Nguyen, Joanne Thanh-Tâm; Ferrière, Amandine; Tabarin, Antoine (Frontiers in Endocrinology, 2024)
This report describes a rare case of a 20-year-old male with an ACTH and prolactinsecreting invasive pituitary macroadenoma causing hyperprolactinemia and Cushing's disease. He was later found to have an AIP mutation. Treatment with cabergoline (1.5 mg weekly) normalized prolactin concentrations and induced a major shrinkage of the adenoma. Not only was urinary free cortisol normalized for more than 14 years but the treatment induced normal hypothalamopituitary-adrenal (HPA) axis function illustrated by the reappearance of a normal cortisol/ACTH circadian rhythm, cortisol suppression to dexamethasone and disappearance of the excessive and aberrant responses to CRH and desmopressin, respectively. This case is the first description of complete restoration of the physiological characteristics of the HPA axis by a medication during the treatment of Cushing's disease. Although exceptional, it illustrates that drugs targeting the pituitary adenoma can bring true complete remission of Cushing's disease.